2020
DOI: 10.1111/hsc.13247
|View full text |Cite
|
Sign up to set email alerts
|

Online health communities, contributions to caregivers and resilience of older adults

Abstract: The aim of this paper is twofold. Firstly, to investigate the potential benefits of online health communities (OHCs) for informal caregivers by conducting a systematic literature review. Secondly, to identify the relationship between the potential benefits of OHCs and resilience factors of older adults. Performing a thematic analysis, we identified the potential benefits of OHCs for informal caregivers of older adults, including two salient themes: (a) caregivers sharing and receiving social support and (b) se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…According to Haugan et al (2020Haugan et al ( , & 2021, the quality of the nurse-patient interaction can significantly improve older adults' physical, emotional, social, functional, spiritual well-being, joy-of-life and self-transcendence in the LTC. In addition, Kamalpour et al (2021) proposed the use of an online community to provide the necessary social support, network and resources to engage older adults meaningfully and reduce their loneliness.…”
Section: Discussion On the Key Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Haugan et al (2020Haugan et al ( , & 2021, the quality of the nurse-patient interaction can significantly improve older adults' physical, emotional, social, functional, spiritual well-being, joy-of-life and self-transcendence in the LTC. In addition, Kamalpour et al (2021) proposed the use of an online community to provide the necessary social support, network and resources to engage older adults meaningfully and reduce their loneliness.…”
Section: Discussion On the Key Variablesmentioning
confidence: 99%
“…The role of spousal relationship was corroborated based on the salutogenic model. According to Kamalpour et al (2021), many older adults might find themselves serving as informal caregivers for their spouses or friends and losing access to environmental resources due to aging‐related issues. However, participation in caregiving does enhance the resilience of older adults by providing them with environmental resources through engagement with the online health community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would be helpful to better understand what other practices may take place in OCs, and how interactions of older adults with caregivers and professionals can affect their resilience. In line with Kamalpour et al (2021), future research should investigate how participation in OCs can support resilience of the caregivers in their caregiving journey. Our findings further showed some older adults engage in disparaging practices such as misconduct.…”
Section: Conclusion and Future Researchmentioning
confidence: 93%
“…smoking) often turn to HSNs to connect with people with similar conditions to share information that could support the self-management of their diseases (Frost & Massagli, 2008;Griffiths et al, 2015;Vassilev et al, 2014;Ventola, 2014). Family members and caregivers also use HSNs to access information that could empower them to support the persons they are caring for (Kamalpour et al, 2021). However, healthcare professionals are generally reluctant to use HSN platforms for direct patient care (Ventola, 2014), though recent studies have shown that some are beginning to use HSNs to communicate with their patients, answer their questions and provide general education on public health issues (Moorhead et al, 2013;Zhou et al, 2018).…”
Section: Provision Of Health Informationmentioning
confidence: 99%